Le développement professionnel dans une perspective constructiviste ou socioconstructiviste : une compréhension conceptuelle pour des implications pratiques - Marilène Gosselin; Anabelle Viau-Guay; Bruno Bourassa (Perspectives Interdisciplinaires sur le Travail et la Santé)
To foster personal well-being at work, some authors suggest focusing on professional development, that is learning that develops a person’s potential to perform work, in line with his/her personal and professional aspirations. However, opinions are mixed regarding which approaches should be favoured, with various notions and mechanisms being promoted in both the literature and organizations. So as to address this issue, this article looks at certain concepts of professional development from a constructivist or socio-constructivist perspective. Based on a literature review, the article establishes that there are mainly two perspectives used to address professional development. Certain concepts and empirical studies are discussed in terms of personal, professional and socio-cultural aspects in an effort to define it from a constructivist or socio-constructivist perspective. Lastly, this article highlights some implications for both research and practice with the aim of better understanding and supporting professional development in the workplace.